Pengaruh Konsentrasi Ruthenium (N719) sebagai Fotosensitizer dalam Dye-Sensitized Solar Cells (DSSC) Transparan: Hardani, Hendra Hendra, Muhammad Iman Darmawan, Cari, Agus Supriyanto - Hardani, Hardani; Hendra, Hendra; Muh. Iman Darmawan, Muh. Iman Darmawan; Cari, Cari; Agus Supriyanto, Agus Supriyanto (Jurnal Fisika dan Aplikasinya, 2025)
DSSC (Dye-sensitized solar cells) is a firmware device capable of converting solar energy into electrical energy by utilizing a ruthenium dye (N719) as a sensitizer. In this research has been successfully made the working electrode is made of titanium dioxide ( TiO2) nanoparticles size shaped thin film is deposited on a transparent conductive glass FTO (fourine-doped tin oxide) by the spin coating method. From the test results using AM 1.5G solar simulator (100 mW / cm2) obtained overall conversion efficiency reached 0.298% with an open circuit voltage (Voc) of 460 mV, short circuit current density (Jsc) of 7.5 mA with a fill factor (FF) 0.24.